2016
DOI: 10.1155/2016/5272531
|View full text |Cite
|
Sign up to set email alerts
|

Calycosin and Formononetin Induce Endothelium‐Dependent Vasodilation by the Activation of Large‐Conductance Ca2+‐Activated K+ Channels (BKCa)

Abstract: Calycosin and formononetin are two structurally similar isoflavonoids that have been shown to induce vasodilation in aorta and conduit arteries, but study of their actions on endothelial functions is lacking. Here, we demonstrated that both isoflavonoids relaxed rat mesenteric resistance arteries in a concentration-dependent manner, which was reduced by endothelial disruption and nitric oxide synthase (NOS) inhibition, indicating the involvement of both endothelium and vascular smooth muscle. In addition, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…In addition to a direct stimulation, formononetin may potentiate the endothelial NO/cGMP pathway by upregulating eNOS at both the mRNA and protein levels [ 167 ]. In human umbilical vein endothelial cells (HUVECs), formononetin increases NO production and upregulates the expression of eNOS and of neuronal NOS (nNOS) without affecting iNOS [ 168 ]. Formononetin is able to increase eNOS expression via activation of the PI3K/PTEN/Akt and MAPK pathways.…”
Section: Vasorelaxant Effects Of Isoflavones In Vitromentioning
confidence: 99%
“…In addition to a direct stimulation, formononetin may potentiate the endothelial NO/cGMP pathway by upregulating eNOS at both the mRNA and protein levels [ 167 ]. In human umbilical vein endothelial cells (HUVECs), formononetin increases NO production and upregulates the expression of eNOS and of neuronal NOS (nNOS) without affecting iNOS [ 168 ]. Formononetin is able to increase eNOS expression via activation of the PI3K/PTEN/Akt and MAPK pathways.…”
Section: Vasorelaxant Effects Of Isoflavones In Vitromentioning
confidence: 99%
“…The ability of FMN to induce endothelial- and NO-dependent vasodilation has been demonstrated in several studies. 24 , 25 , 33 It has also been established that the PI3K/Akt pathway plays a critical role in eNOS expression and NO production. 34 , 35 Thus, we focused on the probable vasodilative effect of FMN and its interaction with the PI3K/Akt signaling pathway in the current study.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Other studies have demonstrated that FMN evokes endothelium-dependent relaxation in rat arterial rings via the upregulation of NO in arterial endothelium through the MAPK pathway, as well as through the stimulation of potassium channels. 24 , 25 However, the precise molecular mechanisms need to be further elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…), Prunus, Pueraria, and Ononis sp. [5][6][7][8]. Isoflavonoid intake in humans is also increasing due to the use of a variety of dairy products, processed food, and food supplements derived from the aforementioned plants [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The data on the effects of individual purified isoflavonoids themselves are hence largely missing, with some exceptions [12]. Additionally, ex vivo and animal vascular studies have been performed for a limited number of compounds [6,11,13,14], and even less information is available in respect to coronary vessels [15][16][17].…”
Section: Introductionmentioning
confidence: 99%